The Actualisation of Muhammad Iqbal’s Islamic Educational Philosophy in the Context of Modern Education - Ansorul Alim; Amri Saputra; Mahmud Arif (PT. Education Research Center, 2025)
This research discusses Muhammad Iqbal’s Islamic educational philosophy and its relevance in the context of modern education. This study is motivated by concerns about the current direction of education, which tends to become trapped in materialistic and instrumental orientations, thereby neglecting the moral and spiritual dimensions of the human being. Using a qualitative approach with a library research method, this study examines Iqbal’s major works such as The Reconstruction of Religious Thought in Islam, Asrar-i-Khudi, and Rumuz-i-BeKhudi, as well as various secondary sources that explore the influence and actualisation of his ideas in the field of education. The findings indicate that Iqbal’s philosophy of education is rooted in the concept of Khudi, namely human self-awareness as a being endowed with creative and spiritual potential to realise divine values in life. According to Iqbal, education must be a process of shaping individuals who are dynamic, independent, and responsible towards themselves and society. He rejects educational models that blunt creativity and focus solely on memorisation, as such approaches distance human beings from their true nature as free and creative beings. In the context of modern education, Iqbal’s ideas are relevant as a foundation for reforming the Islamic education system towards a balance between reason and faith, freedom of thought and moral responsibility, as well as intellectual advancement integrated with spiritual depth. This research emphasises that the actualisation of Iqbal’s thought in modern education can serve as a philosophical basis for developing an educational paradigm that is humanistic, transcendental, and contextual to contemporary challenges. By integrating spiritual values and rationality, Islamic education has the potential to produce individuals who are not only intellectually capable but also possess strong character, faith, and ethical awareness.